The South Asian bibliographer : a list of current publications compiled by the Library of Congress Office, New Delhi.. (Sage Publications, 1998)
Records publications acquired from Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, Sri Lanka, and Tibetan titles issued in India, China, and elsewhere.